PENGARUH DISKON TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK CAMILLE BEAUTY - Halimah, Elma; Musadad, Anwar (Jurnal Manajemen dan Bisnis, 2025)
This study aims to examine the effect of discounts on purchasing decisions for Camille Beauty products. The increasing market competition demands companies to develop effective marketing strategies, one of which is through offering discounts. Based on an associative study with a quantitative approach, data were collected through online questionnaires distributed to Camille Beauty consumers. The results of the simple regression analysis showed that discounts have a significant and positive effect on purchasing decisions, with a coefficient of determination (R²) of 39.1%. This means that 39.1% of the variability in purchasing decisions can be explained by the discount variable. These findings indicate that the larger the discount offered, the higher the tendency for consumers to purchase Camille Beauty products.